United States : Financial Sector Assessment Program-Technical Note-Banking Supervision and Regulation. (IMF Staff Country Reports; Country Report, 2020)
This technical note leverages on the 2015 FSAP which concluded that the United States (U.S.) had a high degree of compliance with the Basel Core Principles (BCPs). The FSAP reviewed the progress achieved in addressing the main weaknesses previously identified and the main supervisory and regulatory developments since then. The key focus are the steps taken by the U.S. authorities in recent years to recalibrate and further tailor the banking regulatory and supervisory framework and the role of stress tests in the supervision process. The FSAP team has not covered the impact of COVID-19 outbreak on banks supervision and has not discussed with authorities the related policy response. The FSAP recommendations are meant to be considered once the impact of the pandemic on the economy and the banking sector becomes clearer.